Evaluation of soybean breeding lineages to new sources of root-knot nematode resistance - Hamawaki,Osvaldo Toshiyuki (2019)
ABSTRACT In Brazil, as the soybean crop expands the losses caused by nematodes as well as its incidence in producing areas have increased. Therefore, this work aimed to develop a non-genetically modified soybean which combines desirable traits as the root-knot nematode resistance, early-maturity, high seed yielding, and high oil and protein contents. Consequently, seeds (F2) derived from the double-crossing between (Guarani x Sambaiba) x (M Soy 6101 x Conquista) were bulked to grow the F3 generation. Following generations were advanced by the SSD method of breeding until F6. Thus, plants showing superior characteristics were planted separately to perform progeny tests and then advanced breeding lines were thoroughly tested and compared to standards in representative environments across several locations in the Midwestern region in Brazil. As a result, we developed an early-soybean with cycle-length of 107 days; usually cycles range from 90 to 160 days. It presents desirable traits as high yield (3677 kg ha-1), Brazilian national average ranged between 2.5 and 3 thousand kg ha-1; broad adaptability, with 19% of oil, and 38.4% of protein on the seeds. Oil and protein standard contents are 20% and 40%, respectively. In addition, it is root-knot nematode (Pratylenchus brachyurus) resistance, not differing statistically (RF = 1.70) from the expected value given by Crotalaria spectabilis (RF = 1.14). Accordingly, we recommend this new cultivar to producers that intend to grow a second crop of either corn or cotton in the summer, or for crop producing areas with high incidence of P. brachyurus.